LIABILITY OF THE HOLDING COMPANY FOR UNLAWFUL ACTIONS IN GROUP COMPANIES (Case Study of Supreme Court Decision Number 89 PK/Pdt/2010 Concerning Violations of Distribution) - Magfirah Bachmid (Faculty of Law, University of Mataram, 2021)
Economic development in Indonesia has progressed significantly from year to year, so has the development of national companies either in the form of a single company, joint venture, or group company in the form of PT, CV and so on. The development referred by this research is the development of group companies consisting of holding companies and subsidiary companies where the leadership system of the group company is centralized so that it has the potential to arise an abuse of authority from the holding company, one of which is illegal acts arising from the legal relationship between the holding company and its subsidiary within the group company. This can be seen in the case decision of the Supreme Court of the Republic of Indonesia No.89 PK/Pdt/2010 between PT. Effem Food, Inc and PT. Effem Indonesia against PT. Smak Snak regarding violations of distribution activity. The purpose of this study was to determine the form of liability from the holding company to the subsidiary in the event of an illegal act in the group company based on the decision of the Supreme Court of the Republic of Indonesia No. 89 PK/Pdt/2010. Based on the Judge’s assessment and consideration of the evidence of losses suffered by the plaintiff, namely PT. Smak Snak, against the bad faith of the defendants, namely PT. Effem Food, Inc. and PT. Effem Indonesia, causing the panel of judges to place joint liability on PT. Effem Food, Inc. and PT. Effem Indonesia for their illegal actions as the holding company against PT. Smak Snak as a subsidiary. This decision is a manifestation of the application of piercing the corporate veil to the holding company and its subsidiary due to the ownership of PT. Effem Food, Inc. over 90% shares of PT. Effem Indonesia, regarding to this case, PT. Effem Food, Inc. acting as the holding company of PT. Effem Indonesia which exercises to control over the operational activities of its subsidiary. This research is a normative research with a conceptual and statutory approach.